The adequacy of the methods used in the collection of tax debt in Iraq: Applied research in the General Authority for Taxation (Journal of Accounting and Financial Studies ( JAFS ), 2019)
If the sovereignty of the state is reflected in the taxation of its citizens, this sovereignty can not be completed and completed only if it works on its part to collect its debts, whether voluntary or compulsory, and the debt of the debt arises from the will of the individual and the will of the state alone, The existing management of seizure and collection is based on an unequal relationship between the State and the debtor from which the obligation arises. Naturally, this relationship has obligations and rights on both parties. The researcher used a set of studies and previous research, books and other sources related to the subject of research. This was done through the theoretical and practical aspects, which focused on direct and indirect collection methods. The statistical program SPSS was used to calculate statistical indicators.The most important conclusions reached by the researcher are:                                • The method of clearing is the easiest and there is the possibility to work, according to the proportion of the views of the sample 71%, who were accounted for accounting (40.4% of the sample), which specialists in the calculation of the tax, and the most economical methods in practice, but it is not implemented in Iraq.• The absence of a higher committee in the General Authority for Taxation is concerned with studying the methods of collecting each type of tax in force in Iraq, to ​​find out the problems and causes.The most important recommendations reached by the researcher are:• The researcher recommends that the tax legislator legislate a legal text to work in the manner of clearing, and build a solid banking system suited to work in this way.Forming a higher committee in the General Authority for Taxation to study the methods of collecting all types of taxes applicable in Iraq, and to identify its problems and methods and develop the necessary treatments to guarantee the rights of the treasury.